Plataforma Watson para internet das coisas - Braga, Luís Maurício (2020)
This project was developed for use in a milking parlor, in the city of Sertão / RS, a municipality that houses a large milk production in the Alto Uruguay region, seeking to bring contributions to this economic activity. The WATSON platform for Internet of Things (IoT) is a managed service, hosted in the cloud, designed to simplify obtaining values from IoT devices. The evolution of the IoT concept occurred due to the convergence of several technologies, such as real-time analysis, machine learning, merchandise sensors and embedded systems. In this sense, the objective of this work was to implement the prototype of a platform capable of establishing interoperability between hardware and software components. A system model based on an IoT architecture was proposed, linked to IBM WATSON technology. From the implementation of the prototype of the IoT platform, linked to the IBM WATSON technology, which interprets the text sent by the user, it was possible to observe that it is able to optimize and facilitate the management of the milk production environment. This platform allows the use of an interface that ensures users a better view of operations and conditions such as temperature, humidity, CO and light, captured through sensors.